Nitric oxide ameliorates zinc oxide nanoparticles phytotoxicity in wheat seedlings: Implication of the ascorbate-glutathione cycle - Tripathi, Durgesh K.; Mishra, Rohit K.; Singh, Swati; Singh, Samiksha; Singh, Vijay P.; Singh, Prashant K.; Chauhan, Devendra K.; Prasad, Sheo M.; Dubey, N K.; Pandey, Avinash C. (Frontiers in Plant Science, 2017)
The present study investigates ameliorative effect of nitric oxide (NO) against zinc oxide nanoparticles (ZnONPs) phytotoxicity in wheat seedlings. ZnONPs exposure hampered growth of wheat seedlings which was coincided with reduced photosynthetic efficiency (Fv/Fm and qP) due to increased accumulation of zinc (Zn) in xylem and phloem saps. However, SNP supplementation has partially mitigated the ZnONPs-mediated toxicity by modulation of photosynthetic activity and Zn accumulation in xylem and phloem sap. Further, the results reveal that ZnONPs treatments enhanced level of hydrogen peroxide (H2O2) and hence lipid peroxidation (as malondialdehyde; MDA) due to severely inhibited activities of the ascorbate-glutatione cycle (AsA-GSH) enzymes: ascorbate peroxidase (APX), glutathione reductase (GR), monodehydroascorbate reductase (MDHAR) and dehydroascorbate reductase (DHAR), and its associated metabolites: reduced ascorbate and glutathione. In contrast to this, the addition of SNP together with ZnONPs maintained the cellular functioning of the AsA-GSH cycle properly, hence lesser damage was noticed in comparison to ZnONPs treatments alone. The protective effect of SNP against ZnONPs toxicity on fresh weight (growth) can be reversed by 2-(4carboxy-2-phenyl)-4,4,5,5-tetramethyl- imidazoline-1-oxyl-3-oxide, a NO scavenger, suggesting role of NO released from SNP in ameliorating ZnONPs toxicity. Overall the results of the present study have shown about implication of NO in the reducing ZnONPs toxicity through the regulation of accumulation of Zn, and functioning of the AsA-GSH cycle.